2007
DOI: 10.1002/ppul.20695
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide combined with prostacyclin and adrenomedullin in acute respiratory failure with pulmonary hypertension in piglets

Abstract: Our aim was to evaluate if the combined inhalation of both nitric oxide (iNO) and aerosolized prostacyclin or iNO and adrenomedullin (ADM) is more effective in lowering pulmonary arterial pressure (PAP) and improving oxygenation than nitric oxide alone in an animal model with pulmonary hypertension (PH). Moreover, we studied the effect on pulmonary mechanics, surfactant activity, and pulmonary oxidative stress of the different treatments. Twenty-eight piglets with acute lung injury induced by lung lavages with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Lung function was preserved at most time points, with lung mechanics of the prostacyclin analogue‐treated group in early inflammatory phase (days 7, 14) approaching control values. Our results are supported by previous findings reporting the effects of inhaled PGI 2 on lowering airway resistance and improving lung compliance in a PH model 27 . Additionally, another PGI 2 analogue was recently shown to maintain lung function in BLM‐challenged mice 28 and COX 2 ‐derived prostacyclin managed to prevent BLM‐induced pulmonary fibrosis using genetically modified mice 10 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lung function was preserved at most time points, with lung mechanics of the prostacyclin analogue‐treated group in early inflammatory phase (days 7, 14) approaching control values. Our results are supported by previous findings reporting the effects of inhaled PGI 2 on lowering airway resistance and improving lung compliance in a PH model 27 . Additionally, another PGI 2 analogue was recently shown to maintain lung function in BLM‐challenged mice 28 and COX 2 ‐derived prostacyclin managed to prevent BLM‐induced pulmonary fibrosis using genetically modified mice 10 .…”
Section: Discussionsupporting
confidence: 91%
“…Our results are supported by previous findings reporting the effects of inhaled PGI 2 on lowering airway resistance and improving lung compliance in a PH model. 27 Additionally, another PGI 2 analogue was recently shown to maintain lung function in BLM-challenged mice 28 and COX 2 -derived prostacyclin managed to prevent BLM-induced pulmonary fibrosis using genetically modified mice. 10 Overall, accumulative data support that administration of prostanoids can be beneficial to lung function, a phenomenon also supported by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely, therefore, that the beneficial effects of iNO on pulmonary function in this model of chronic lung disease reflect primarily nonsurfactant actions, such as anti-inflammatory [27][28][29][30][31] and antioxidant actions [32][33][34][35] . These results are in agreement with the observation that iNO increases lung compliance and tidal volume, and decreases airway resistance, without affecting surfactant surface activity in an animal model of acute lung injury [56] .…”
Section: Ino Therapy and Surfactantsupporting
confidence: 82%
“…ADM and ADM2 have organ-protective effects in animals with heart failure, myocardial infarction, stroke, resistant hypertension, pulmonary arterial hypertension, preeclampsia, secondary lymphedema, or diabetic ulcer [ 19 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. These peptides may prevent organ injuries by improving endothelial cell functions and vascular barrier integrity and reducing oxidative stress as well as by improving cardiac output and renal glomerular filtration [ 6 , 72 , 73 , 74 , 83 , 96 , 97 , 98 , 99 , 100 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, ADM was shown to improve hemodynamics and renal functions in patients with heart failure or pulmonary hypertension [ 72 , 76 , 85 , 86 , 87 , 101 ] and decrease pulmonary vascular resistance and arterial pressure in patients with pulmonary hypertension [ 83 , 87 , 120 ]. However, the development of therapeutic ADM peptides was largely bogged down in the last decade because these peptides have short half-lives (i.e., ~20 min) and may induce compensated tachycardia at pharmacological doses [ 72 , 73 , 74 , 75 , 76 , 83 , 101 ].…”
Section: Discussionmentioning
confidence: 99%